PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DENGAN TWO STAY TWO STRAY TERHADAP HASIL BELAJAR SISWA - Megawati, Megawati; Kune, Syarifuddin; Rahmatia Thahir (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The type of research is a Quasy Experimental Designwhich aims to determine comparison of the Group Investigation Cooperative Learning Model with Two Stay Two Stray Model on Student Learning Outcomes of Biology Digestive System Concepts in Class XI SMAN 3 Gowa. The population this study were all students of class XI MIA SMAN 3 Gowa and the sample of this study was Class XI MIA 1 as the experimental I which was given the Group Investigation learning model and XI MIA 2 with the Two Stay Two Stray model as the experimental II with technique sampling using random sampling. The data collected is about student learning outcomes which are then analyzed using descriptive statistical and inferential statistical. The results showed that the percentage value of students' completeness in the posttest experimental I was 10.59% of students who completed while in the experimental II, 10.57% of students who completed. The results of the t-test using the independent t-test showed the results of 0.096, so 0.000 <0.05, the hypothesis of this study was accepted.